ANALISIS PRODUKSI KOPI DI DESA BOCEK KECAMATAN KARANGPLOSO KABUPATEN MALANG - Ahmad Junaidi; Wahyu Hidayat Riyanto (Jurnal Ilmu Ekonomi JIE, 2017)
Abstract: This study aims to analyze the production of coffee in Bocek village – Karangploso sub-district – Malang regency in one season. The data used is primary data, primary data obtained through field interviews directly to 35 coffee farmers. The results showed that the average production of coffee in Bocek Village in one season was 6000 kg. The total cost incurred to process one hectare of coffee land in one season in Bocek Village is Rp. 35.600.700, while the total revenue received by coffee farmers in processing one hectare of coffee land of Rp. 168.000.000, so the net income received by coffee farmers in processing one hectare of coffee is Rp. 132.399.300. Based on regression analysis, Cobb-Douglas production function model explain that LnQ = LnA + αLnK + βLnL  shows variable of land area (1,369331) and labor (0,280272) in one season has significant effect to coffee production. Each 1% increase of land area will increase coffee production by 1,393%. Each labor increase of 1% will lead to an increase in coffee production by 0.282%. Statistical analysis shows the value of determination coefficient (R2) is 0.9633 and the value of the probability of F-statistic test is significant at α 5%. Keywords: production coffee, function production cobb-douglas, land area, labor.